Improvement in the Yield and Selectivity of Lactulose Synthesis with Bacillus Circulans β-galactosidase - Vera-Vera, C (Academic Press, 2020)
A commercial preparation of β-galactosidase from Bacillus circulans was evaluated as catalyst in the synthesis of lactulose considering temperature, pH, initial total sugar concentration, enzyme to initial lactose mass ratio and fructose to lactose molar ratio (F/L) as variables. The results obtained in terms of selectivity (SLu) yield (YLu) and productivity (πLu) of lactulose synthesis showed that only the initial total sugar concentration and lactose to fructose molar ratio were significant, the latter strongly affecting SLu. Best results were obtained at F/L of 20, being YLu = 0.54, πLu = 0.043 g h−1·mg enz−1, and SLu = 30.9. Under these conditions lactulose synthesis was favored over transgalactosylated oligosaccharides (TOS), due to the higher chance of transferring the galactosyl group into fructose at high F/L. Yields of lactulose and TOS depended on the enzyme origin, while their maximum concentrations were obtained at different lactose conversions (at 0.7 for lactulose and at 0.45 for TOS) and depended on the kinetics of reactions. Yields attained with Bacillus circulans β-galactosidase are higher than obtained with enzymes from other origin at comparable conditions, so this system is a preferred option for lactulose production. © 2019 Elsevier Ltd